MEMBANGUN CITRA INDUSTRI MEDIA MELALUI CORPORATE SOCIAL RESPONSIBILITY (CSR) - Cosmas Gatot Haryono (SEMIOTIKA: Jurnal Komunikasi, 2013)
Disaster often come in Indonesia extend widely effect to society especially to escalate solidarity within Indonesia’s nation. Media as part of society, is take part to alleviate burden from the victim of disaster with establish activity of facilitation fund raising from audience. The fund is managed until arrive at victim of disaster which need aids quickly, appropriately and accountable. Managing the facilitation of humanity fund raising which done correctly, transparent and accountable will elevate the company image on society. Related with that, in this article, will be analyzed about strategy is done in managing the facilitation of humanity fund raising. This article showing that what media done through CSR activity really influence society perception towards media itself. A media is not assumed same with other media which publish or broadcast news and entertainment, instead of as media that care about society of disaster-stricken. This concern is present positive image for media at public.Keywords: Image, CSR, Media Management